Auxiliary clitics in Polish - Dorota Jagódzka (LingBaW)
Polish auxiliary clitics constitute an interesting set of data which draws attention to cross-linguistic differences among Slavic languages. A general principle for clitic placement in Indo-European languages is the one described by Jacob Wackernagel in his 1892 work. He concluded that clitics appeared in the second position in the clause, after the first word in a sentence. This pattern was true to some degree in Old Church Slavonic and still holds for a number of contemporary Slavic languages e.g. Serbo-Croatian, Slovene, Czech and Slovak which have second position clitics. Bulgarian and Macedonian have verb adjacent pronominal clitics and Polish has auxiliary clitics (Migdalski 2007, 2010, Pancheva 2005). Also in the older versions of Polish language the above mentioned tendency was strong.